Monotonic Response of Beams Castedwith Different Types of Concrete - Makhool, Assel Qaddoori; Mohammed, Zainab A.; Atiyah, Hiba Akram (Al-Nahrain Journal for Engineering Sciences, 2025)
Structural elements. This means the structural behavior can be quantified by considering the behavior of each structural element in each load path. Concrete is a material known for its great strength. Regardless, there are a few weaknesses, which must be taken in consideration in the design of concrete structural elements. Basically, concrete is made of three main ingredients: Portland cement, water, and aggregates (sand and stone).In order to improve tensile strength and ductility (capacity to stretch and deform prior to failure) in concrete, so this paper discus some types of concrete and record the effect on beams. Reactive powder concrete (RPC) is an actual concrete mixture, it is a special type of concrete because mix concrete (coarse and fine aggregate ) replaced by fine sand size (150-400)µm. In the experimental comparison the mechanical properties( compressive , splitting tensile and flexural )strength of plain RPC and high and normal strength concrete. Each set consisted of (4) cubes of (100×100×100_mm, (8) cylinder of (150×300mm) and (4) prism of (100x100x500) mm and consisted of (4) beam of (1000×100×400)mm. The results shown that the maximum compressive strength is 107 MPa and the maximum splitting tensile 9 MPa of RPC comparison high and normal strength concrete. The result of the second part shown increased RPC reinforced concrete the firstcrack288 MPa and ultimate crack 380MPa comparison high and normal strength concrete and the mode of failure of RPC (flexural-shear).